Genetic Diversity and Inbreeding Depression of Domestic Group of Stingless Bees (Tetragonula fuscobalteata) in Thailand - ชื่นป้อม, นิภา; Volkaert, Hugo; บุญเกิด, สมนึก (Princess of Naradhiwas University Journal, 2018)
Stingless bees (Tetragonula spp.) are in the same family as honey bees but without a sting. They can be a perfect pollinator in the nature as same as bees. Stingless bee is one of the important insect for the forest ecosystem. The rapid changes of environment are the major impact on population and the way of living of stingless bee in Thailand. Limitation of place for livelihood and decrease in food sources caused the extinction of stingless bee. Therefore, this research aim to study on the genetic diversity and inbreeding coefficient of domestic group of stingless bees in Thailand. Total 9 beehives of stingless bees were collected from southern and western of Thailand. Three SSR (Simple Sequence Repeat) primers were used toidentify DNA polymorphism. The results showed that the samples collected from nearby areas of the same province had closely relationship at 91.97%. Whereas stingless bee from neighboring province Chumphon and Prachuap Khiri Khan had inbreeding coefficient 45.59%.